Health Impacts of Climate Change on Farmers in Agricultural Communities - Enggal Hadi Kurniyawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Sa Sa Aung; Madiha Mukhtar (Health and Technology Journal (HTechJ), 2026)
Climate change increasingly affects agricultural systems and the health of farmers who depend directly on environmental conditions. This study aimed to systematically review recent evidence on the impacts of climate change on farmers’ health and its implications for agronursing. A systematic review was conducted following the PRISMA 2020 guidelines using three databases: Scopus, PubMed, and ProQuest. Articles published between 2025 and 2026 that met predefined inclusion criteria were selected, and their methodological quality was assessed using the Joanna Briggs Institute critical appraisal tools. The search identified 6,262 records, and 10 studies met the eligibility criteria for final analysis. The findings indicate that climate change affects farmers’ health through multiple pathways, including heat stress, food insecurity, environmental exposure, and psychological distress. Several studies also highlight the importance of knowledge, coping strategies, and community adaptation in improving farmers’ resilience. Climate change poses significant challenges to farmers' health. Agronursing plays an important role in promoting occupational and mental health, and in supporting community-based adaptation strategies to improve the well-being of farming communities.